2015
DOI: 10.1242/jeb.120402
|View full text |Cite|
|
Sign up to set email alerts
|

Size dependence in non-sperm ejaculate production is reflected in daily energy expenditure and resting metabolic rate

Abstract: A number of minor errors were published in J. Exp. Biol. 218, 1410-1418 The corrected sections are reproduced below, with changes highlighted in bold. These changes do not affect the conclusions of the paper. RESULTS Metabolic substrates: respiratory quotientMean respiratory quotient (RQ=VĊ O2 /VȮ 2 , where VĊ O2 is the rate of CO 2 production and VȮ 2 is the rate of O 2 consumption) across treatments and size classes was 0.743. Mean RQ of the mating males (median=0.71) was significantly lower than that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 92 publications
(147 reference statements)
0
19
0
Order By: Relevance
“…Females mate faster with large than with small males (the present study and Pitnick ), and small males lose out in competition with large males (Partridge, Ewing & Chandler ), so it may pay small males to invest heavily in any matings achieved, as has been argued for similar patterns found in garter snakes ( Thamnophis sirtalis parietalis ; Friesen et al . ). In contrast, large males that may have multiple mating opportunities might risk ejaculate depletion if they do not partition their ejaculate (Hihara ; Linklater et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Females mate faster with large than with small males (the present study and Pitnick ), and small males lose out in competition with large males (Partridge, Ewing & Chandler ), so it may pay small males to invest heavily in any matings achieved, as has been argued for similar patterns found in garter snakes ( Thamnophis sirtalis parietalis ; Friesen et al . ). In contrast, large males that may have multiple mating opportunities might risk ejaculate depletion if they do not partition their ejaculate (Hihara ; Linklater et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, there is currently limited data available on the costs of Sfp production (Perry, Sirot & Wigby ; Friesen et al . ; Sirot & Wolfner ). Furthermore, traits involved in post‐copulatory interactions are often subject to strong stabilizing selection (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The very existence of male mate choice, rather than indiscriminant mating (Drickamer et al, ; Gowaty et al, ; Edward and Chapman, ), and evidence that males adjust their ejaculates when presented with sub‐optimal mating opportunities (Pizzari et al, ; Delbarco‐Trillo and Ferkin, ; Ramm and Stockley, ; Lüpold et al, ; DelBarco‐Trillo, ; Ramm et al, ) together imply that ejaculates are physiologically expensive and are conserved whenever possible (Parker, ; Parker and Pizzari, ). Indeed, direct calorimetric study revealed that a single copulatory plug in garter snakes might represent 5–18% of an animal's daily energy budget (Friesen et al, ). To our knowledge, no equivalent study has been performed in a mammal, partly because it is currently not possible to separate the cost of seminal fluid versus spermatogenesis, as can be achieved in snakes (Friesen et al, ).…”
Section: Transglutaminasementioning
confidence: 99%
“…Indeed, direct calorimetric study revealed that a single copulatory plug in garter snakes might represent 5–18% of an animal's daily energy budget (Friesen et al, ). To our knowledge, no equivalent study has been performed in a mammal, partly because it is currently not possible to separate the cost of seminal fluid versus spermatogenesis, as can be achieved in snakes (Friesen et al, ). Nevertheless, the relatively high rate of protein turnover by seminal vesicles may enable the dynamic allocation of resources by mammals (Claydon et al, ).…”
Section: Transglutaminasementioning
confidence: 99%
“…sperm and seminal fluid production; e.g. Dewsbury, ; Olsson et al ., ; Friesen et al ., ) and precopulatory sexually selected traits (i.e. weapon development, display traits and associated behaviours; e.g.…”
Section: Introductionmentioning
confidence: 99%